Mothers' preventive health care practices and children's survival in Burkina Faso: Findings from repeated cross-sectional household surveys - Badolo Hermann; A Sathiya Susuman; Bado Aristide Romaric; Hien Mwinonè Hervé (Comparative Population Studies (CPoS), 2020)
The significant reduction in the level of child mortality in both developed and developing countries over recent decades has led to an improvement in children's health. The implementation, monitoring, and evaluation of the health programs needed to reduce child mortality require determination and an understanding of the factors responsible for this reduction. This study investigated factors that have contributed to the recent improvement in the survival of children under five, focusing on the contribution of preventive health care in improving children's survival rates in Burkina Faso. The data used come from baseline and end-line surveys designed to evaluate the impact of performance-based financing (PBF) on health programs in Burkina Faso. Using time-series for health districts and child-level logistic regression models, we estimated the effect of preventive health care, as summarized by the changes in the composite coverage index (CCI), on under-five child survival of temporal trends and covariates at the household, maternal, and child levels. At the health district level, a unit increase in standardized CCI was associated with an improvement in under-five child survival after adjustment for survey period effects. The linear regression analysis showed that a standardized unit increase in CCI was associated with an increase in the percentage of children under five who survive. At the child level, the logistic regression showed that a skilled attendant at birth (SBA), wealth index, and mother's parity were associated with under-five children's survival, after adjustment for the survey period effects and a set of household, maternal, and child-level covariates. Preventive health care is important in improving under-five children's survival, whereas the effects of economic growth in Burkina Faso remain weak and inconsistent. Improved coverage of preventive health care interventions are likely to contribute to further reductions in under-five mortality in Burkina Faso.
urn:nbn:de:bib-cpos-2020-19en0
Keywords: 300; Child mortality; Preventive health care; Maternal and child health interventions; Burkina Faso